Diseño de modelo sistémico para mitigar la deserción escolar en gestantes a temprana edad (2021)
The project is the result of the research process focused on mitigating the impact of the increase in the dropout rate of pregnant women at an early age in Colombia, specifically will focus and develop in the city of Bogota, comprising mainly the area of education in public schools. It is here that I approach the study of the project from the perspective of Industrial Design, I identify the problem that falls on the lack of correct and adequate provision of information to the student, the disruption in the connections that the student and support entities should have, generating different links that are non-existent and detaching a single problem that could be solved if dealt with accordingly.